2018
DOI: 10.18203/2394-6040.ijcmph20182493
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fish oil supplementation in patients with rheumatoid arthritis

Abstract: Many clinical trials of omega-3 fatty acids, supplied as fish oil supplements, have been carried out in rheumatoid arthritis (RA) over the past 3 decades. The current analysis evaluates the influence of omega-3 polyunsaturated fatty acids on clinical results in patients with rheumatoid arthritis. We conducted the current meta-analysis using a comprehensive search of EMBASE, MEDLINE, PubMed, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials till 31 January 2018 for rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In a meta-analysis of the findings of rheumatoid arthritis patients, Barkoot and colleagues showed that omega 3's PUFAs have a significant influence on non-steroidal anti-inflammatory drug (NSAID) consumption (Standardized mean differences −0.52, 95% CI: −0.92 to −0.12, P = 0.01) and pain (Standardized mean differences −0.55, 95% CI: 0.17-0.027, P = 0.57). Hence, consuming omega 3's PUFAs in doses higher than 2/7 daily for more than 3 months effectively reduces consuming NSAIDs in rheumatoid arthritis patients (25). Lee and colleagues conducted a meta-analysis to evaluate the effects of omega 3 PUFAs on the clinical results of rheumatoid arthritis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of the findings of rheumatoid arthritis patients, Barkoot and colleagues showed that omega 3's PUFAs have a significant influence on non-steroidal anti-inflammatory drug (NSAID) consumption (Standardized mean differences −0.52, 95% CI: −0.92 to −0.12, P = 0.01) and pain (Standardized mean differences −0.55, 95% CI: 0.17-0.027, P = 0.57). Hence, consuming omega 3's PUFAs in doses higher than 2/7 daily for more than 3 months effectively reduces consuming NSAIDs in rheumatoid arthritis patients (25). Lee and colleagues conducted a meta-analysis to evaluate the effects of omega 3 PUFAs on the clinical results of rheumatoid arthritis patients.…”
Section: Discussionmentioning
confidence: 99%